Identification of dementia and MCI cases in health information systems: An Italian validation study - Ilaria Bacigalupo; Flavia L. Lombardo; Anna Maria Bargagli; Silvia Cascini; Nera Agabiti; Marina Davoli; Silvia Scalmana; Annalisa Di Palma; Annarita Greco; Marina Rinaldi; Roberta Giordana; Daniele Imperiale; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction The identification of dementia cases through routinely collected health data represents an easily accessible and inexpensive method to estimate the prevalence of dementia. In Italy, a project aimed at the validation of an algorithm was conducted. Methods The project included cases (patients with dementia or mild cognitive impairment [MCI]) recruited in centers for cognitive disorders and dementias and controls recruited in outpatient units of geriatrics and neurology. The algorithm based on pharmaceutical prescriptions, hospital discharge records, residential long‐term care records, and information on exemption from health‐care co‐payment, was applied to the validation population. Results The main analysis was conducted on 1110 cases and 1114 controls. The sensitivity, specificity, and positive and negative predictive values in discerning cases of dementia were 74.5%, 96.0%, 94.9%, and 79.1%, respectively, whereas in detecting cases of MCI these values were 29.7%, 97.5%, 92.2%, and 58.1%, respectively. The variables associated with misclassification of cases were also identified. Discussion This study provided a validated algorithm, based on administrative data, which can be used to identify cases with dementia and, with lower sensitivity, also early onset dementia but not cases with MCI.